THE CHILD JUSTICE ACT: A DETAILED CONSIDERATION OF SECTION 68 AS POINT OF DEPARTURE WITH RESPECT TO THE SENTENCING OF YOUNG OFFENDERS - Stephan Terblanche (Potchefstroom Electronic Law Journal, 2012)
The Child Justice Act 75 of 2008 establishes a criminal justice system for child accused, separate from the criminal justice system which continues to apply for adult accused in South Africa. The Act aims to keep children out of detention and away from the formal criminal justice system, mainly through diversion. When these interventions would be inadequate or unsuccessful, the Act provides for child offenders to the tried and sentenced in child justice courts. Until now there has been little discussion of the details of the provisions dealing with sentencing.Sentencing in a child justice court is regulated by chapter 10 of the Act and section 68 is the first section in this chapter. This section effectively amounts to the “jurisdictional” provision of the new child sentencing system: it not only mandates child justice courts to impose their sentences in terms of the Act, but also provides the first set of boundaries (or the first part of the framework) within which sentencing should take place. Despite its brevity, section 68 is not without interpretative challenges. Of course, it has to be interpreted within the context of the entire Act. Explaining this context is the first function of this article. The various aspects of section 68 are further critically explored and discussed.